Cellulose Nanofiber Platform for Electrochemical Sensor Device: Impedance Measurement Characterization and Its Application for Ethanol Gas Sensor - Rakhmania, Citra Dewi; Sari, Shaimah Rinda; Azhar, Yosyi Izuddin; Sugita, Airi; Tominaga, Masato (Universitas Negeri Padang, 2022)
Bioplastics such as cellulose nanofibers (CNF) are widely used in daily life as an alternative to plastics. CNF is also considered a biodegradable, readily disposable, and low-cost material, making it suitable as a sensor platform. The mechanically treated CNF has both hydrophobic and hydrophilic properties where the hydrophobic sides bond strongly with MWCNTs to provide conductivity on the CNF sheet, while the hydrophilic sides allow the target component to be adsorbed on its laminated structure and react with the electrode surface. From an electrochemical measurement of ferricyanide solution indicated that the MWCNTs modified CNF could act well as electrode. Furthermore, the thin-sheet electrode successfully detected ethanol based on a direct electron transfer (DET) between PQQ-ADH and the MWCNTs on the electrode surface. Aside from its lightweight properties, the developed CNF electrode possesses excellent stretchability, flexibility, and adjustability to human skin, making it ideal for a future wearable skin gas sensor.